Risk in child protection assessment challenges and frameworks for practice - Calder, Martin C.; Archer, Julie (Assessment in childcare series., 2016)
In this accessible guide to assessing risk in child protection, Martin C. Calder outlines the relevant policy, introduces debates about what risk means, identifies the key challenges for practice, summarizes the evidence base for effective assessment and provides a helpful framework for front line workers.